Finland : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 1996)
This Selected Issues paper and Statistical Appendix examines inflation and wage dynamics in Finland. The paper discusses the data set used (quarterly data covering from 1975 to 1995) and the statistical properties of the relevant time series. It presents the model and the empirical estimates, and provides an outlook for consumer price index and nominal wage inflation for 1996:Q1-2001:Q4. The paper examines the determinants of the equilibrium real exchange rate, and also analyzes the Finnish banking system and the credit crunch hypothesis.